The impact of cooking and delivery modes of thymol and carvacrol on retention and bioaccessibility in starchy foods. (1st April 2016) - Aravena, Gabriela; García, Olga; Muñoz, Ociel; Pérez-Correa, José R.; Parada, Javier
Highlights: Release of thymol and carvacrol is affected by processing conditions. Boil cooking generated higher retention. Bioaccessibility was slightly dependent on cooking and inclusion modes. Results could be explicated by interaction of molecules with biopolymers like starch. Abstract: Oregano and thyme possess beneficial properties for human health, mainly attributable to monoterpenes such as thymol and carvacrol. The main objective of this research was to assess, on starchy food, the impact of cooking (boiling and baking) and delivery (ground leaves and essential oil) modes on retention and bioaccessibility of thymol and carvacrol. Retention was assessed after cooking, while bioaccessibility was estimated in cooked samples using an in vitro digestion model. Our results indicate that bioaccessibility was weakly dependent on cooking and delivery modes (27–33%). Boil cooking presented 20% more retention than baking for both compounds. When essential oil was added to the food matrix, thymol was retained almost 25% more when compared with ground leaves' addition. Conversely, carvacrol was retained 39% more when ground leaves were added.